Modeling the diffusion of generation products in the presence of heterogeneous strategic customers for determining optimal marketing-mix strategies. (October 2021) - Najafi-Ghobadi, Somayeh; Bagherinejad, Jafar; Taleizadeh, Ata Allah
Highlights: Modeling the diffusion of generation products when customers are strategic. Investigating optimal dynamic pricing and advertising decisions, simultaneously. Considering two types of advertising: direct and word-of-mouth. Using the Pontryagin's maximum principle to analyze the proposed model. Providing a heuristic solution algorithm to solve numerical examples. Abstract: It is well-known that customers' strategic behaviors can influence the diffusion of new products and, consequently, firms' profit. Thus, firms should consider the strategic behaviors of customers for making their marketing decisions. In this paper, we proposed a new diffusion model for generation products by considering heterogeneous strategic customers and two key marketing variables of pricing and advertising. It was shown that optimal pricing trajectory is a concave curve and there is a threshold for the optimal advertising trajectory. When customers are strategic, firms' optimal response is to decrease the advertising expenditure and price. We found that the advertising expenditure increases with increasing the discount rate, number of population size, and effectiveness of advertising. Also, firms should reduce the advertising expenditure when the impact of word-of-mouth advertising is high. Among other findings, it was shown that discount rate has a negative effect on the price. Further, higher advertising effectiveness could lead to higher price.